Building a Mobile Reporting Dashboard System Based on Android Using Web Service Restful for Congregation Data - Dody Ivana; Budi Susanto; Yuan Lukito (Universitas Kristen Satya Wacana, 2022)
The development of the Church is increasingly growing marked by the increasing number of people who attend the church. The church needs to utilize technology in paying attention to spiritual growth in existing congregations. But to do that, there needs to be a system that can see data that is well visualized and can be used by the church. It is not easy to visualize data manually so a practical and portable system is needed. The purpose of this study is as a material consideration in seeing the development of the Church in the Church and improve efficiency without having to use a computer. The process of gathering congregational data comes from the data warehouse of the Indonesian Christian Church Synod in the Central Java Region which is obtained from the Church Information System called SISWA which is local in every church. The interface design process is also carried out using User Centered Design which is centered on the user. This system will be designed using Resrful web Service which has better capabilities than other web services. By building this system, it can facilitate the church in seeing the development of the church and can be taken into consideration in making decisions by the church.